Accreditation of flow cytometry in Europe1. Issue 3 (28th March 2013) - Sack, Ulrich; Barnett, David; Demirel, Gulderen Yanikkaya; Fossat, Chantal; Fricke, Stephan; Kafassi, Nikolitsa; Nebe, Thomas; Psarra, Katherina; Steinmann, Jörg; Lambert, Claude
Abstract: ISO 15189 has been introduced to enable any clinical laboratory, irrespective of geographic location, to be accredited against internationally recognized standards and therefore facilitate direct international comparison of laboratories. Together with increasing use of ISO 15189 for standardization and competition purposes, often triggered by demands of patients and clinicians, clinical flow cytometry laboratories are becoming increasingly challenged to introduce compliant quality management systems. Whilst in most countries, ISO 15189 accreditation is not yet compulsory, there is increasing evidence to suggest that the implementation of this standard is growing. As a result, the European Society of Clinical Cell Analysis (ESCCA) has analysed the impact of accreditation in clinical flow cytometry laboratories. It found, through a discussion forum, that staff qualification, adaptation of multicolour antibody panels, and implementation of a comprehensive quality system (including quality assessment) have been identified as major challenges. © 2013 International Clinical Cytometry Society